Clinical safety of England's national programme for IT: A retrospective analysis of all reported safety events 2005 to 2011. Issue 3 (March 2015) - Magrabi, Farah; Baker, Maureen; Sinha, Ipsita; Ong, Mei-Sing; Harrison, Stuart; Kidd, Michael R.; Runciman, William B.; Coiera, Enrico
Highlights All known safety problems with national scale IT systems in England over 6-years were examined. National IT implementation was associated with problems on a large scale impacting on care delivery. Problems encountered are not unique, but are well-understood challenges of IT implementation. Human factors were four times as likely to result in reported patient harm than technical problems.